Modeling of operational control of the oxygen regime of the aquatic ecosystem in the conditions of the Dnieper basin - Ponomarenko, Roman; Plyatsuk, Leonid; Tretyakov, Oleg; Ablieieva, Irina (Видавництво Львівської політехніки, 2020)
The article investigates the adequacy of the mathematical model of oxygen regime prediction in the Dnieper basin, based on the classic Streiter-Phelps model. Retrospective analysis of the Dnieper oxygen parameters with further verification of the Streeter- Phelps model adequacy for the Dnieper basin conditions was used. The mathematical model of the dynamics of the integral indices of the ecological state of the reservoir (the Streeter-Phelps model) has been improved by supplementing the corrective coefficients, which allows predicting with sufficient accuracy the change of the Dnieper ecological state.
Keywords: Dnieper basin; ecological state; anthropogenic load; quality assessment; quality forecast